Ks. prof. Aleksy Klawek i początki Biblii Poznańskiej - Kapera, Zdzisław J. (Collectanea Theologica, 2018)
The Rev. Prof. Aleksy Klawek (1890-1969) was a great Polish Old Testament scholar who can certainly also be called a great Hebrew scholar. His dream was to create a modern translation of the Bible directly from Hebrew, Aramaic and Greek, and Poland had long been in need of one, as Wujek’s translation of 1597 was outdated and not easy to understand. But it took Klawek years before he decided to present his first fragmentary translations; this happened in the late 1930s and 1940s. It is not clear why Klawek did not join the team of translators of the so-called “Tyniec Bible”, now known as the “Millennium Bible”, in 1959, but being aware of the weakness of Father Augustyn Jankowski’s translating team, Klawek formed his own team before the publication of the “Millennium Bible” composed mostly of his former Ph.D. students. In the end, we did not receive a modern translation of the Bible from Klawek’s hands as he died in 1969. His idea was put into practice under the editorship of his pupil Michał Peter and Marian Wolniewicz. As Klawek’s translations of Psalms, Song of Songs and Daniel remained unfinished, all that the editors could do was to gratefully acknowledge Klawek’s initiative. The new “Poznań Bible”, which appeared in the years 1974-1976, is much prized for its quality (clarity and accuracy) and its extensive commentaries.